Revealing the Essence of Geographical Factors in Regional Income Formation. - Lasaiba, Mohammad Amin (Universitas Pattimura, 2023)
In the era of global economic dynamics, geographical factors have proven to be crucial variables that shape a region's identity and distinct characteristics. This article aims to elucidate the fundamental impacts of geographical factors on regional income. This research is a literature review conducted by analyzing and evaluating relevant written sources concerning the studied topic or issue. The analysis results reveal that complex topography and extreme climatic conditions can create unique economic opportunities and challenges within a region. The interplay of these geographical factors forms a distinct narrative about the economic development of a region. Abundant natural resources offer significant income potential, yet prudent management is necessary for long-term economic sustainability. Coastal regions provide essential trade and tourism opportunities, and marine resources become valuable assets in boosting coastal region income. However, wise protection and management are required to avoid negative impacts. Technology and its access play a crucial role in economic growth